Monetary Regime Choice in Singapore: Would a Tayor Rule Outperform Exchange-Rate Management? - CHOW, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2013)
This paper adopts a dynamic stochastic general equilibrium-vector autorgressive (DSGE-VAR) approach to examine the managed exchange-rate system at work in Singapore. We examine if the country has any reason to fear floating the exchange rate and adopting a Taylor rule. Our results show that, in terms of overall inflation volatility, the exchange rate rule has a comparative advantage over the Taylor rule when export price shocks are the major sources of real volatility, while a Taylor rule dominates when domestic productivity shocks drive real volatility. The exchange-rate rule also dominates the Taylor rule for reducing inflation persistence.